Gender asymmetries in Portuguese trade unions: the case of the CGTP-IN - Santos, M. H. (2021)
Gender imbalances persist throughout the world, particularly at leadership level, and equally also visible in the case of trade unions. This article focuses on CGTP-IN, the largest Portuguese trade union confederation, and sets out analysis incorporating both figures from this organisation and accounts by female members of CGTP-IN unions. Results confirm the existence of gender asymmetries, especially at the highest leadership levels. Analysis of the discourses of these women leaders reveals some awareness of the influence of gender on professional relations, placing women at a disadvantage, especially where leadership is concerned. Furthermore, four reasons driving the persistence of these gender asymmetries in trade union leadership/decision-making roles were identified: family responsibilities, gendered professional segregation, masculine trade union cultures and traditional gender stereotypes. Nevertheless, the interviewees resist to means of affirmative action such as gender quotas, and instead prefer to prioritise education and raising awareness around gender equality.